Primary Thyroid Schwannoma with Papillary Carcinoma and Hurtle Cell Adenoma in a Background of Hashimoto’s Thyroiditis: A Very Rare Occurrence - Mishra, Shilpa; Waghmare, Tejaswini; Taware, Annapurna (Annals of Pathology and Laboratory Medicine, 2019)
Schwannomas are common benign neurogenic tumours that arise from Schwann cells of nerve roots; up to 45% arise in head and neck. However primary thyroid schwannomas are extremely rare. Among thyroid tumours papillary carcinoma of thyroid (PCT) are the most common. Hurthle cell neoplasms are also rare. In addition occurrence of all the three neoplasms in the same patient is extremely rare. In this report we discuss a case of left lobe intrathryroidal schwannoma with papillary carcinoma of thryroid (PCT), Hurthle cell adenoma and background Hashimoto thyroiditis in a 25 year old female. On FNAC it was diagnosed as colloid nodule with cystic change, total thyroidectomy was done and histopathological examination showed that the largest well circumscribed nodule was a benign neurogenic tumour, schwannoma (left lobe of thryroid gland). There were other smaller thyroid nodules; one showing papillary carcinoma with lymph node metastasis and other showing hurthle cell adenoma with background Hashimoto’s thyroiditis.